Pengaruh Faktor-Faktor Produksi Gambir terhadap Tingkat Pendapatan Petani Gambir - Mariana Manik (Universitas 45 Surabaya, 2024)
This study aims to analyze the factors that influence gambir production and the income of gambir farmers in Bandar Baru village. Data was collected through a questionnaire using a Likert scale, involving 95 respondents selected via purposive sampling. The analysis was conducted using multiple linear regression with SPSS version 25. The results indicate that price (X1), labor productivity (X2), and production costs (X3) simultaneously and significantly affect the income of gambir farmers (Y) in Bandar Baru village, as evidenced by an F-value of 69.582, which is greater than the F-table value of 2.679. Labor productivity, when analyzed partially, does not significantly affect the income of gambir farmers, as indicated by a t-value of 1.219, which is less than the t-table value of 1.919, with a significance level below 0.05.Conversely, price has a partial significant effect on the income of gambir farmers, with a t-value of 2.463, exceeding the t-table value of 1.919, and a significance level below 0.05. Production costs also have a partial significant effect on the income of gambir farmers, evidenced by a t-value of 3.446, which is greater than the t-table value of 1.919, with a significance level below 0.05.The results from the coefficient of determination (R) test indicate that the Adjusted R Square value is 0.624, meaning that 62.4% of the income level (Y) can be explained by the variables of labor productivity (X1), price (X2), and production costs (X3), while the remaining 37.6% can be attributed to other factors not examined in this study.